Augmented Spaces and Maps - Schranz, Christine (De Gruyter, 2020)
With the convergence of space, media and design, not only are design practices radically changing but so are the surfaces that need to be designed: digital maps enable an interface to the physical world and allow new forms of navigation and spatial experience. At the same time, internet companies as cartographers raise discussions about inequalities and hegemonic claims. This book introduces this field, outlines important influences, theories and approaches and uses current examples to explain how card-based interfaces can work. This basis also serves as an inspiration for a critical and experimental approach that is important for designers, practitioners and an audience interested in design.